Registration of Transfer of Land Ownership Due to Inheritance in order to Ensure Legal Certainty - Desi Redhawati; Iyah Faniyah (Master of Law Program, Ekasakti University, 2024)
Land is the highest value of wealth and is also a source of life. To prevent disputes from occurring, the Government will hold land registration in accordance with article 19 paragraph (1) of the UUPA. The transfer of land rights is the transfer/transfer of land rights from the old right holder to the new right holder. Based on Article 42 paragraphs (1) and (2) of Government Regulation Number 24 of 1997 concerning Land Registration regulates the obligation of heirs to register the transfer of their rights to the Land Office. But the reality is that there are still many heirs who have not registered their transition eventhough there are clear rules that regulate it. The approach method uses the normative juridical approach as the main approach supported by the empirical juridical approach. Based on the results of the discussion and analysis, it is concluded as follows: First, the registration of the transfer of ownership of land due to inheritance in order to ensure legal certainty, based on the completeness of the rights, must meet 2 (two) conditions, namely the material condition and the immaterial condition.But in reality, there are still many heirs who have not registered the transfer of their rights. The causative factors include: the level of public education is still low so that there is a lack of legal awareness about the importance of land registration, the cost of managing certificates is expensive, not all heirs have the cost for the transition process, ignorance of land registration requirements and procedures. Second, as a result of the law, there is a transfer of ownership of land because the heirs are the heirs as the holders of the right to get legal protection because materially and immaterially, the rights and obligations of the heirs are directly transferred to the heirs.